If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8n-6(n+4)=-(-8+2n)
We move all terms to the left:
8n-6(n+4)-(-(-8+2n))=0
We add all the numbers together, and all the variables
8n-6(n+4)-(-(2n-8))=0
We multiply parentheses
8n-6n-(-(2n-8))-24=0
We calculate terms in parentheses: -(-(2n-8)), so:We add all the numbers together, and all the variables
-(2n-8)
We get rid of parentheses
-2n+8
Back to the equation:
-(-2n+8)
2n-(-2n+8)-24=0
We get rid of parentheses
2n+2n-8-24=0
We add all the numbers together, and all the variables
4n-32=0
We move all terms containing n to the left, all other terms to the right
4n=32
n=32/4
n=8
| -3=x-5/7 | | 70=28-14x | | 12a+4a*4a+9=0 | | 1/3x+1/4x=2x-17 | | 6y−3=6y+8 | | 42x+158=1166 | | 8x^2-48x=-135 | | 6y+5+5Y+7=15y-20 | | 129=3(8+5p) | | 2x/3=12/9 | | 4(v-2)=28 | | 17y=119 | | 3(4t-4)=10t1=7+2t | | x/4-8=-13 | | 8x2+2x-6=0 | | 5(2/5x-3)=4x+15 | | 6-7(6-6n)=-3n+9 | | (2x+1)/100=x | | (x+42)+2x=90 | | 5-8(a-3)=93 | | n=15÷-3 | | 5k=8(k+3) | | 9-2(5x+4)=6-4(3x+7)+2x | | 4-6x=-x-6x | | 6x+7=4×-5 | | -35+5x=6(x-5) | | 510=8x | | 2x-4=31-3x | | 3(x+2)+4x-5=7(x+1-6 | | 7x+6=3(5x-4)-10 | | 9x-5+4x=7×+43-2x | | -5m-2(m-3)=-8-m+4 |